Preference, Challenges, and Satisfaction with Using E-Books: Is There a Gender Difference among Omani Nursing Students? - Thanka, Anitha Nesa; Natarajan, Jansirani; Joseph, Mickael Antoine (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Objectives: As technology becomes increasingly popular among millennial nursing students, publishers are transitioning towards electronic textbooks (e-books). E-books have advantages for long-term learning and budget control compared to conventional printed textbooks. This cross-sectional descriptive study examined the perceived usefulness, challenges, and satisfaction with e-books compared to printed textbooks, among Omani nursing students. Methods: Data was collected from a convenience sample of 77 students who used e-books in a community health nursing course using a valid and reliable survey in the fall 2020 semester. Results: Results showed that despite reporting more challenges with printed textbooks, the majority of students (74%) preferred printed textbooks. Additionally, 71.4% of students had a low level of satisfaction with e-books. Female students had a higher preference for printed textbooks and lower satisfaction with e-books compared to male participants. Conclusion: More research is needed to understand the reasons behind students’ preference for printed textbooks, and to investigate the gender differences observed in this study.